Discovery and Characterization of a New Group of IS10 Insertion Sequences - (:unkn) unknown (My University, 2016)
Insertion sequences (ISs) are small mobile genetic elements that can have significant impact on the genotype and phenotype of a host organism. Previous work in this laboratory revealed an insertion sequence that disrupted the luxA gene in Vibrio harveyi strain BCB451, knocking out light production. Phylogenetic analysis of this insertion sequence, dubbed IS451, reveals that it is in the IS10 family, but represents a novel variant that is only 79% identical to other known IS10 sequences. Twelve copies of IS451 were isolated from a genomic library and sequenced, and were found to be essentially identical, but located in dispersed chromosomal locations. We find that of all the copies sequenced, luxA is the only structural gene disrupted by IS451. All other copies are inserted into intergenic regions. Screening of 1,107 additional bioluminescent strains isolated from the same geographical location indicates that IS451 is rare. Of the two isolates that contain IS451, both have an abnormally large number of IS10s within their genomes. While isolating IS451 from positive isolates, three other novel IS10 sequences were discovered. These insertion sequences, designated IS226-A, IS226-B, and IST2-8, are only 88%, 79%, and 84% similar to other known ISs, respectively. Together with IS451, these insertion sequences are included in the subgroup of IS10s which includes the IS10s that make up the Tn10 transposon. The three isolates that contain these ISs are all within the genus Vibrio, but represent different species.
Keywords: Evolution; Insertion Sequence; IS10; Transposase; Vibrio